Pengembangan Potensi Wisata Embung Desa Siraman dan Pengenalan serta Pencegahan Stunting - Larasati, Stephani Rangga (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Community service activities from Atma Jaya University Yogyakarta have the theme KKN Society 5.0. This theme was raised because of the Covid 19 pandemic, so that this service activity had to be carried out without direct dropping into the village that would be used as a research site. This time, one of the community service groups was group 53, which saw the potential of the village of Siraman, Wonosari, Gunung Kidul. Using secondary data search methods, it was found that there is potential in the tourism sector and there are health sector problems. In the tourism sector, the group chooses to develop water tourism and arts potential, while in the health sector, an introduction and prevention program will be held. The existence of Embung Banon Senja, batik jarik, and jathilan in Siraman Village can be one way to attract tourists, especially from outside the village, so that Siraman Village can be better known, besides Siraman Village has a problem in the form of a high stunting rate which attracts our group's attention. From the above topic, a program was made to develop tourism potential and counseling in the health sector in the form of E-books and videos. The hope is that the making of this E-Book and video can be used as a reference and reference in the development and development of Siraman Village so that it is more widely known and can reduce the number of stunting that occurs in the village. Keywords — embung, batik jarik, stunting, Siraman Village